The Effect of Motivation and Work Discipline in Improving Employee Work Quality: A Case Study of KFC Lubuklinggau - Maresta Dora; herma yunita (Jurnal Media Ekonomi (JURMEK), 2026)
The goal of this study is to determine if motivation and work discipline impact employee job quality (a case study of KFC Lubuklinggau). This study employs a non-probability saturation technique and comprises three factors: motivation variables (X1), work discipline variables (X2), and work quality variables (Y). This study conducts its analysis using quantitative testing. The demographic and data samples were analyzed using multiple linear regression. All KFC Lubuklinggau employees, a total of 30 respondents, were used as saturation samples. This study employs multiple linear regression analysis, validity and reliability tests, hypotheses, F tests, and T tests. The findings show that motivation and work discipline have both partial and simultaneous effects on employees’ work quality. In the t-test, the motivation variable (X1) had a significance value of 0.05, or the calculated t-value was greater than the t-table value, with 3.797 > 1.703. The work discipline variable (X2) also had a significance value of 0.05, or the calculated t-value was greater than the t-table value, with 3.719 > 1.703. For the F-test, the significance value was 0.000, which is less than 0.05. The estimated F-table result shows that the calculated F-value was greater than the F-table value, with 53.636 > 3.35